Pengaruh Pelatihan dan Motivasi Terhadap Kepuasan Kerja serta Dampaknya pada Kesejahteraan Pengrajin Batik di Sentra Kecamatan Pelayangan Kota Jambi - Amirah, Amirah; Bukit, Pantun; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2024)
The enhancement of society through local economic development is crucial in fostering the productivity of the community by providing various facilities that support its existence, not excluding institutions or industrial centers. Training and motivation are essential for creating job satisfaction, which in turn contributes to overall well-being. Therefore, this research aims to analyze the influence among the variables, both directly and indirectly. This study is categorized as descriptive and inductive research. It was conducted in the Batik industry center in the Pelayangan Subdistrict of Kota Jambi, with a population and sample of 80 batik employees. The research analysis employs the path analysis method.